Use of Cashless Payments in MSMEs in the Pall Beach Tourism Area, Marinsouw Village - Karla Arina, Kristi; Hanna Lintong, Elsje; Juandy Livingstone Rompas, Jeifer; Rommy Novie Korua, Sammy; Aprilia Maramis, Pingkan; Maria Christianto, Virginia; Cindy Wangko, Jennifer (Journal of Accounting and Finance Management, 2024)
Study This aiming for analyze adoption cashless payment technology by MSMEs in the Village Marinsouw, a area ongoing tourism developing in North Sulawesi. With use method qualitative and approach studies case, research this involving interviews and observations direct with UMKM owners, stakeholders interests, as well as tourists who become user main cashless payment. Data analyzed in a way thematic use device soft Nvivo For identify theme key like adoption technology, challenges, and impact from implementation of cashless payments operational business and satisfaction customers. Research results show that factor main influencing factors level adoption are Usage Rate (UR) and type cashless services used, especially QRIS. Technological Barriers (TB), such as problem network, and Trust in the System (TS) is still become challenge significant , although support government (Government Support - GS) is proven help speed up adoption. Cashless payment is proven increasing Operational Efficiency (OE) and Increased Income (II) for MSMEs, while from perspective tourists, Ease of Use (EU) and Customer Satisfaction (CS) become factor booster main.